UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MELALUI METODE BERMAIN KARTU KATA - Muzaqi, Ahmad Imam Muzaqi; Maysun, Siti Nuriyah (Hamka Ilmu Pendidikan Islam, 2025)
One of the rapidly developing abilities of children during preschool age is language skills. Language acquisition is closely related to cognitive abilities. A child's speech structure reflects their thinking structure. Good language skills will help them adapt to their environment and become communicative individuals. These language skills include listening, speaking, reading, and writing. The purpose of this study was to improve learning outcomes in early reading skills through word card games for children aged 5-6 at PAUD A Al Qolam Preschool. This study was a classroom action research model following the Kemmis and Taggart model. This study included two cycles, each with four stages: planning, implementation, observation, and reflection. The results showed a significant increase in early reading skills in Group B students. This was indicated by an increase in percentages from the pre-cycle, cycle I, and cycle II in the learning process carried out through word card games. Thus, it can be concluded that the research hypothesis, which states that word card games can improve children's reading skills, is supported.